IMPLEMENTASI TOOLS EXPERT SYSTEM BUILDER UNTUK MENENTUKAN TINGKAT KETAHANAN PANGAN DI WILAYAH KOTA DEPOK - Ratih Titi Komala Sari; Fauziah (Jurnal Ilmiah Informatika, 2016)
Food is a basic component to create quality human resources as well as the main pillars of national development that plays a role in maintaining the stability of the economic, social, and national food security. National food security starts from compliance with food in the smallest area as a base of agricultural activities. Base area development has the objective to achieve food security in a region that has the integration of infrastructure ranging from the aspect of availability to the consumption of food to meet and achieve food security of households. Regional food security system needs updating software technology as a form of comprehensive evaluation in order to optimize the regional food security system by connecting the data supporting food security in a region information using expert system, in this case using the tools Expert System Builder Interface Unit with Visual Basic programming. The result is a public information about food security, especially in the city of Depok in an effort to evaluate and monitor the various indicators of food security, in order to prepare food security policies required by the policy makers.